Effect of Polypropylene Microplastic and Florfenicol Antibiotic on Some Hormonal and Haematological Biomarkers in Yellowfin Seabream (Acanthopagrus latus) - Mehrnaz Shirmohammadi; Farahnaz Kianersi; Nima Shiry; Fatemeh Hekmatpour (Aquatic Sciences and Engineering)
Microplastics (MPs) and antibiotics, such as florfenicol (FFC), are emerging pollutants affecting aquatic ecosystems. This research examined the separate and joint impacts of MPs and FFC on hematological and hormonal indicators in yellowfin seabream (Acanthopagrus latus). The fish were categorized into four groups according to their dietary treatments: a control group with a standard diet and three experimental groups receiving diets containing 15 mg/kg of FFC, 100 mg/kg of MPs, or both for 10-day. The ELISA method was used to measure hormones in plasma. Blood collection occurred on the first, fourth, seventh, and fourteenth days after feeding stopped to evaluate FFC concentration in the plasma and various hematological and hormonal parameters. Exposure to FFC and MPs, alone or together, considerably decreased red blood cell, hemoglobin levels, hematocrit values, mean corpuscular hemoglobin, mean corpuscular hemoglobin, white blood cell, lymphocyte, and erythropoietin concentrations. Neutrophil and cortisol levels increased. Mean corpuscular volume was elevated only in the group receiving both FFC and MPs. After a 14- day recovery period, all measured parameters returned to baseline levels in the FFC-only group. Co-exposed group showed the highest concentration of FFC in the plasma on the first day. The groups administered MPs, individually or collectively, exhibited a reduction in thyroid hormones. These findings indicate that both MPs and FFC induce anemia and stress in yellowfin seabream, with co-exposure exacerbating these effects. Although the toxic effects of FFC were temporary, the lasting presence of MPs indicates potential long-term risks.